VHI: THE ASSESSMENT OF CURRENT SITUATION AND THE DEVELOPMENT PROSPECTS OF PAID MEDICAL SERVICES - B. A. Vasserman (Сеченовский вестник, 2022)
The problems of voluntary health insurance and assessment of current situation and the development prospects of paid medical services are raised in this article.